Analysis on Assets Liability Management under Fluctuating Interest Rate Condition - Handoyo Prakoso (Business and Entrepreneurial Review, 2006)
The purposes of this study are to identify influence of interest rate fluctuation to Government Bank profitability and the sensitiveness to its liabilities and assets. and examine assets liability policy in fluctuating interest rate condition at government bank management. Data are obtained from government bank financial statetment for period of 1999-2003 and l-month SBI's interest rate for period of 1993-2003. Analysis applied in this study is balanced analysis, ratio analysis, statistical analysis and funds gap management method. Based on the analysis, it is found that fluctuating interest rate has impact on government bank assets and liabilities management, and the position of government bank funds gap for period of 1999-2003 is negative. Under such circumstances, the application of funds gap management method to the fluctuating interest rate is needed accordingly for optimum profit.